2014
DOI: 10.1111/jspn.12074
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to children's use of speech‐generating devices: a descriptive qualitative study of mothers' perspectives

Abstract: Nurses can use the list of barriers and facilitators provided here as a springboard to discuss the families' experiences with device use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
1
23
0
2
Order By: Relevance
“…Studies conducted after this systematic review have suggested a variety of additional environmental factors which may influence family experiences with high-tech AAC systems. Crisp, Draucker, and Ellett (2014) investigated barriers and facilitators to the use of speech generating devices by children aged 5 to 23 years. Factors of influence within the theme of products and technology that had not already been discussed by Baxter et al (2012) included the device start-up time, colour, number of USB ports, and the presence of additional functions such as the internet (Crisp et al, 2014).…”
Section: Stakeholder Experiences With Aacmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies conducted after this systematic review have suggested a variety of additional environmental factors which may influence family experiences with high-tech AAC systems. Crisp, Draucker, and Ellett (2014) investigated barriers and facilitators to the use of speech generating devices by children aged 5 to 23 years. Factors of influence within the theme of products and technology that had not already been discussed by Baxter et al (2012) included the device start-up time, colour, number of USB ports, and the presence of additional functions such as the internet (Crisp et al, 2014).…”
Section: Stakeholder Experiences With Aacmentioning
confidence: 99%
“…Crisp, Draucker, and Ellett (2014) investigated barriers and facilitators to the use of speech generating devices by children aged 5 to 23 years. Factors of influence within the theme of products and technology that had not already been discussed by Baxter et al (2012) included the device start-up time, colour, number of USB ports, and the presence of additional functions such as the internet (Crisp et al, 2014). Parents appreciated device trials; however, most families did not receive financial support for the purchase of the device.…”
Section: Stakeholder Experiences With Aacmentioning
confidence: 99%
See 3 more Smart Citations